Theoretical Underpinnings of Jobs Diagnostics - Lachler, Ulrich (The World Bank, 2020)
This paper is a work-in-progress and was developed to advance our thinking on how to make Jobs Diagnostics more strategic and to explore how guidance can best bridge the link from jobs analysis through prioritization, to recommendations. It will continue to evolve as we undertake more diagnostics. The role of Jobs Diagnostics is to help operational teams think more deeply about evidence, guide them towards priority problems and understand the constraints to better jobs outcomes with economic growth, and their likely causes. We believe a better link from standardized diagnosis to recommendations is needed, while recognizing that a single formulaic framework is not desirable. In general, Jobs Diagnostics guidelines should help contribute to thinking about causes of jobs problems identified in data tests, with priorities for policies and operations should be based on evidence and not be left too open to discretion. This is a first attempt to help practitioners narrow down Jobs problems, think deeply about their causes, and prioritize between possible solution areas. Thus, the examples given in this paper are not exhaustive, and its recommendations are not meant to be prescriptive. The guidance will be refined in the coming years, as more practical examples emerge and we gain further lessons in strategic prioritization